2010
DOI: 10.1111/j.1365-2265.2010.03873.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in Rotterdam criteria and metabolic risk factors in a multiethnic group of women with PCOS studied in Denmark

Abstract: To cite this version:Dorte Glintborg, Hanne Mumm, David Hougaard, Pernille Ravn, Marianne Andersen. Ethnic differences in Rotterdam criteria and metabolic risk factors in a multiethnic group of women with PCOS studied in Denmark. Clinical Endocrinology, Wiley, 2010, 73 (6) Design: Retrospective trans-sectional study.Patients: 1002 premenopausal women with the diagnoses hirsutism or PCOS were divided according to ethnicity: Caucasian (CA, n=784), Middle East (ME, n=190), Asian (n=14), other (n=14).Measurements:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 30 publications
5
47
1
Order By: Relevance
“…PCOS is a heterogeneous disease, but we did not classify our patients due to the clinical phenotypes. Secondly, since most of the original studies derived from European population and the metabolic parameters seemed to be different in PCOS patients with different ethnic descents [44][45][46][47], our findings may not be extended to other descent. Thirdly, due to the limited numbers of original researches enrolled, our results are not conclusive.…”
Section: Discussionmentioning
confidence: 79%
“…PCOS is a heterogeneous disease, but we did not classify our patients due to the clinical phenotypes. Secondly, since most of the original studies derived from European population and the metabolic parameters seemed to be different in PCOS patients with different ethnic descents [44][45][46][47], our findings may not be extended to other descent. Thirdly, due to the limited numbers of original researches enrolled, our results are not conclusive.…”
Section: Discussionmentioning
confidence: 79%
“…The relative risk for obesity was higher in Caucasian women compared with Asian women, whereas central obesity was comparable in the two groups (4). North European women with PCOS were significantly older and more obese, had higher blood pressure, a more adverse lipid profile and smoked at a higher frequency by the time of referral compared with women originating from the Middle East, for whom insulin sensitivity was higher (36). Immigrants in Western countries may be at increased risk for lifestyle diseases such as obesity and diabetes (60).…”
Section: Cardiometabolic Disease In Pcosmentioning
confidence: 93%
“…Guidelines recommended prospective yearly measurements of blood pressure in women with PCOS (32), but limited data supported that these recommendations should be applied in all women with PCOS. In a Danish study population of women with PCOS, the prevalence of systolic blood pressure >130 mmHg was 46.3% and diastolic blood pressure >85 mmHg was 37.6% (36). A Dutch study reported increased risk of hypertension especially in young patients with PCOS, but patients with PCOS were more obese than controls (40).…”
Section: Cardiometabolic Disease In Pcosmentioning
confidence: 99%
See 1 more Smart Citation
“…PCOS women in Europe showed differences in lipid values. Namely, while triglycerides were almost universally elevated in PCOS women, in some Caucasian populations HDL was significantly lower and LDL higher in comparison with other populations or reference controls (179,180). Detailed assessment of the prevalence of different patterns of dyslipidaemia is still needed.…”
Section: Role Of Lipo-oxidative Stressmentioning
confidence: 99%